Development trajectories of fatigue, quality of life, and the ability to work among colorectal cancer patients in the first year after rehabilitation: first results of the MIRANDA study - Vlaški, Tomislav; Slavic, Marija; Caspari, Reiner; Fischer, Harald; Brenner, Hermann; Schöttker, Ben (Cancers, 2023)
Cancer-related fatigue, low quality of life (QoL), and low ability to work are highly prevalent among colorectal cancer (CRC) patients after tumor surgery. We aimed to analyze their intercorrelations and trajectories in the first year after in-patient rehabilitation in the German multicenter MIRANDA cohort study. Recruitment is ongoing, and we included the first 147 CRC patients in this analysis. Participants filled out questionnaires at the beginning of in-patient rehabilitation (baseline) and at 3, 6, 9, and 12 months after the baseline. The EORTC-QLQ-C30-General-Health-Status (GHS)/QoL, the FACIT-F-Fatigue Scale, and the FACIT-F-FWB-ability-to-work items were used to evaluate QoL, fatigue, and ability to work, respectively. The fatigue and QoL scales were highly correlated (r = 0.606). A moderate correlation was observed between the fatigue and ability to work scales (r = 0.487) and between the QoL and ability to work scales (r = 0.455). Compared to the baseline, a statistically significant improvement in the QoL, ability to work, and fatigue scales were observed at the 3-month follow-up (Wilcoxson signed rank test, all p < 0.0001). The three scales plateaued afterward until the 12-month follow-up. In conclusion, fatigue, QoL, and ability to work were highly interrelated, improved quickly during/after in-patient rehabilitation, and did not change much afterward in German CRC patients.